A CASE STUDY OF LUNTIAN MULTI-PURPOSE COOPERATIVE IN BARANGAY LALAIG, TIAONG, QUEZON, PHILIPPINES: A VERTICAL INTEGRATION APPROACH - Perilla, M.V.; Escala, J.M.; Setiadi, A. (Diponegoro University, 2009)
The Luntian Multi-Purpose Cooperative located in Tiaong, Quezon, Philippines. The Luntian MultiPurposecooperative focuses more on feed production as well as hog fattening. The LMC applied thevertical integration to develop the cooperative. They have their members as their primary costumers of theirfeeds. The cooperative’s business activity includes also meat shop, granting of production loan, microfinance,mobilization of saving deposits, aside from feed milling and hog fattening. Different agencies, industryorganizations and private institutions provide trainings, seminars, assistance, as well as credit for thecooperative.The aims of the study was to determine the present and discuss a noteworthy business issue (s)of Luntian Multipurpose Cooperative, evaluate the business environment prevailing at a particular time ofthis case , assess the cooperative’s performance in terms of the four business functions , define the problemrelevant to the business issue(s) being studied. The study used primary and secondary data. Primary datawere gathered through interviews with the key personnel, managers, and other informants of the LuntianMultipurpose Cooperative in order to obtain responses regarding the overall status of the cooperative includingits problem and plans. Secondary data were taken from files and documents, especially the history, backgroundinformation and financial statements. Other data were taken through research materials such as book,unpublished special problems and from some government institutions. The recommendation of this researchshowed that Luntian MPC should engage in establishing a communal farm as to become the primary sourceof hybrid piglets that their members would raised. The alternatives solution was establishing a breeding farmthat would ask for initial investment.